A very low central oxygen mass in the peculiar type Ia SN 2010lp: further diversity at the low-luminosity end of SNe Ia. Issue 4 (16th February 2022) - Mazzali, P A; Benetti, S; Stritzinger, M; Ashall, C
ABSTRACT: A nebular spectrum of the peculiar, low-luminosity type Ia supernova 2010lp is modelled in order to estimate the composition of the inner ejecta and to illuminate the nature of this event. Despite having a normally declining light curve, SN 2010lp was similar spectroscopically to SN 1991bg at early times. However, it showed a very unusual double-peaked [O i ] $λ λ \, 6300, 6363$ emission at late times (Taubenberger et al.). Modelling of the nebular spectrum suggests that a very small amount of oxygen (∼0.05 M⊙ ), expanding at very low speed (≲ 2000 km s −1 ) is sufficient to reproduce the observed emission. The rest of the nebula is not too dissimilar from SN 1991bg, except that SN 2010lp is slightly more luminous. The double-peaked [O i ] emission suggests that SN 2010lp may be consistent with the merger or collision of two low-mass white dwarfs. The low end of the SN Ia luminosity sequence is clearly populated by diverse events, where different channels may contribute.